Early Clinical Outcomes of Surgical Management following Vacuum-Assisted Closure in Poststernotomy Mediastinitis - Rafik F. Soliman; Hatem M. Soltan; Saeed O. Abdelwahed; Ibrahim M. Khalil (SVU - International Journal of Medical Sciences)
Background: Poststernotomy mediastinitis, commonly called deep sternal wound infection (DSWI), is a highly concerning complication that can occur in individuals who have undergone cardiac surgery. The optimal way for management is still not well established; antibiotics and frequent debridement followed by surgical closure are the mainstay for better outcomes. Objectives: To assess the outcome of early surgical debridement vacuum-assisted closure (VAC) for the management of mediastinitis following cardiac surgery. Patients and methods: This prospective study, including 32 patients with DSWI, was performed at Menoufia University Hospital between March 2021 and October 2023. All patients were managed using VAC of the wound for 5–7 days, followed by surgical closure. Results: A total of 32 patients presented with DSWI after elective (87.5%) and emergent (12.5%) cardiac surgery. There were 18 male patients and 14 female patients, with ages ranging from 38 to 74. VAC was used for 5–7 days after surgical debridement, and then surgical closure was done directly (18.8%) or using pectoral (56.2%) or omental flap (25%). Conclusion: Our study supported VAC therapy as a safe and effective management for DSWI. VAC decreased the mean hospital stay, wound size, and reinfection rate.